2021
DOI: 10.1007/s13592-021-00881-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of climate seasonality and vegetation cover on floral resource selection by two stingless bee species

Abstract: The response of two stingless bees (Tetragonisca angustula and Melipona eburnea ) to changes in vegetation cover was evaluated on seasonal and spatial scales. Seasonal variation was analysed for 15 months, with monthly melitopalinological assessments of hives located in three different vegetation covers: forests, fallows, and grasslands, in the Colombian Central Cordillera. Fallows, with an intermediate disturbance degree, presented the highest pollen taxa richness for both bee species (33 and 40 taxa for M. e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…The floristic preferences of T. angustula are related to the different climatic periods and to the specific characteristics of the plants during these periods, which are related to the availability of nectar and pollen, as well as to the reproductive strategy of the plants and this bee species. In the study by Prado et al., [30] it was found that during periods of drought, T. angustula showed a preference for flowers of the species Miconia prasina (Sw.) DC. and Ilex laureola Triana & Planch.…”
Section: Resultsmentioning
confidence: 98%
“…The floristic preferences of T. angustula are related to the different climatic periods and to the specific characteristics of the plants during these periods, which are related to the availability of nectar and pollen, as well as to the reproductive strategy of the plants and this bee species. In the study by Prado et al., [30] it was found that during periods of drought, T. angustula showed a preference for flowers of the species Miconia prasina (Sw.) DC. and Ilex laureola Triana & Planch.…”
Section: Resultsmentioning
confidence: 98%
“…However, the availability of various families of these plants contributed to the pollen that was collected. The high availability of plant species in the forest areas was influenced by the higher preference of stingless bees (Prado et al 2021).…”
Section: Areamentioning
confidence: 99%